Evaluation of planting design for cajuput development (Melaleuca cajuputi Powel) in KPH Bojonegoro - Pandu Yudha Adi Putra Wirabuana; Ronggo Sadono; Dewanto (Foresty Faculty of Hasanuddin University, 2021)
Development of cajuput plantation currently becomes the most important activity in KPH Bojonegoro since it provides an essential contribution to maintain the future viability of company. However,the growth performance of cajuput stand relatively varies one of which is influenced by planting design. This study aims to determine the optimum planting design for supporting cajuput stand development. It was conducted by evaluating two different planting designs that generally used for cajuput establishment, namely C1 (spacing 3 m x 1 m) and C2 (spacing 5 m x 1.5 m x 1.5 m). Five parameters were used to evaluate the growth performance and oil production of cajuput stand for each planting design, i.e., survival rate, quadratic mean diameter, basal area, harvesting biomass, and cajuput oil production. Data were collected by field measurementusing a sampling plot 50 m x 50 m with six replications for each planting design. Comparisonmean of cajuput growth performance between two planting designs were analyzed separately for each parameterusing t-test. Results documented there were not a significant different for all parameters, except survival rate. The planting design C2 generated higher survival rate (94.9%) than planting design C1 (64.7%).The planting design C2 was recommended for cajuput development in KPH Bojonegoro. Besides requiring the lower planting density, the use of planting design C2 can optimize land utility with a similar productivity to planting design C1.